2020
DOI: 10.1021/acsaem.0c02442
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Durable Polymers with Enhanced Toughness and Elasticity for Application in Flexible Li-Ion Batteries

Abstract: Next-generation wearable devices compel the development of lithium-ion batteries (LIBs) that can afford mechanical flexibility while remaining safe and stable energy sources. In conventional battery designs the electrode coatings are susceptible to fracture and disintegration when exposed to cyclic flexure. This results in capacity loss, resistance increases, and severely limits their cycle life. Polyurethane (PU) has been investigated as a battery binder but without research into the variety of chemistries av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Many researchers have confirmed that an appropriate binder in the electrolyte is conducive to the transmission of ions and electrons. 45 Based on this, the following experiment was carried out: The SH and SH-ECH films of equal masses and sizes were placed into beakers containing the same volume of electrolyte. The films were taken out after the same amount of time.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Many researchers have confirmed that an appropriate binder in the electrolyte is conducive to the transmission of ions and electrons. 45 Based on this, the following experiment was carried out: The SH and SH-ECH films of equal masses and sizes were placed into beakers containing the same volume of electrolyte. The films were taken out after the same amount of time.…”
Section: Resultsmentioning
confidence: 89%
“…The contact angles on the SH and SH-ECH films both became 0 after 1 s, which indicated a good affinity between the electrolyte and the binders. Many researchers have confirmed that an appropriate binder in the electrolyte is conducive to the transmission of ions and electrons . Based on this, the following experiment was carried out: The SH and SH-ECH films of equal masses and sizes were placed into beakers containing the same volume of electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…The binder physically stabilizes the electrode and plays a key role in improving the energy density and controlling the long-term cycling stability by maintaining the durability of the electrode through the adhesion between the particles. Therefore, the stability of the secondary battery upon prolonged cycling can be maintained by understanding the role of the binder and improving its performance. The binder must be electrochemically stable because it is subjected to a wide voltage range during charging and discharging. Hence, it should allow the maintenance of the electrode structure without undergoing additional oxidation or reduction, in addition to the active material, during charging and discharging.…”
Section: Introductionmentioning
confidence: 99%
“…They have wide applications in biomedical fields, [1][2][3][4] sustainable plastics/elastomer, [5][6][7][8][9][10][11][12] and solid electrolytes [13,14] or DOI: 10.1002/macp.202200079 electrode binders. [15] Among various copolymers, block copolyesters can combine the properties of the respective homopolymers to furnish a new set of functionalities and exhibited adjustable and extensive macroscopic properties because of the block incompatibility. [16][17][18][19][20][21][22][23][24] Especially, block copolymers with highly reactive maleate or fumarate sequences in backbone enables further enhancement of polymer properties through post-polymerization modifications, and thus have attracted increasing attentions in recent years.…”
Section: Introductionmentioning
confidence: 99%